THE ROLE OF DESIGN IN MARKETING - Kostina , Anastasiia; Gorlatova , Elena (Collection of scientific papers «ΛΌГOΣ», 2022)
Original design is an important part of marketing in any company. The development and coordination of the design of any materials, logo, product design - is in itself, part of marketing. If you pay attention to the market leaders, the clue element of their success is excellent design. The importance of design manifests itself in the fact that sellability to 86% depends on the visual perception of the buyer.[1] Proper advertising, pleasing packaging design, originality and recognizability attract attention and increase the likelihood of purchasing goods or services.